Platform Literasi Cloud dalam Mendukung Kegiatan Membaca Nyaring Anak TK Tunas Gama Kabupaten Jepara - Astutik, Leny Suryaning; Dwinata, Anggara; Af’idah, Noer; Wahyuningsih, Endah Tri (Universitas Nusantara PGRI Kediri, 2025)
Literacy is one of the skills in children's reading skills. Currently, children are less motivated to read, so applications are needed that support children's reading skills. This research aims to describe the use of the cloud literacy platform in supporting the reading aloud activities of Tunas Gama Kindergarten children in Jepara Regency. The learning journey continues to be innovative and dynamic, children at the Kindergarten level must continue to improve their literacy skills. Literacy skills are very important in building children's intellectual and language culture so that they think correctly and can be held accountable. By providing cloud literacy platform media, it can at least provide something interesting so that children can read interesting story books on the platform. The research approach used is a qualitative study with a narrative study research design. The research was carried out at Tunas Gama Kindergarten in the 2024 academic year with primary data including teachers and children aged 4-6 years. Data collection techniques obtained through observation, documentation studies, and field notes. The research results show that through cloud literacy platform facilities it can at least support children in reading aloud activities on an ongoing basis. The use of cloud literacy media is an effective component in increasing success in children's language development process. The conclusions from the research show that there is a significant influence from the use of the cloud literacy platform in supporting children's reading aloud activities, so that children's literacy skills become significant.